Allometric escape from acoustic constraints is rare for frog calls. Issue 8 (7th March 2020) - Tonini, João Filipe Riva; Provete, Diogo B.; Maciel, Natan M.; Morais, Alessandro Ribeiro; Goutte, Sandra; Toledo, Luís Felipe; Pyron, Robert Alexander
Abstract: Allometric constraint is a product of natural selection and physical laws, particularly with respect to body size and traits constrained by properties thereof, such as metabolism, longevity, and vocal frequency. Allometric relationships are often conserved across lineages, indicating that physical constraints dictate scaling patterns in deep time, despite substantial genetic and ecological divergence among organisms. In particular, acoustic allometry (sound frequency ~ body size) is conserved across frogs, in defiance of massive variation in both body size and frequency. Here, we ask how many instances of allometric escape have occurred across the frog tree of life using a Bayesian framework that estimates the location, number, and magnitude of shifts in the adaptive landscape of acoustic allometry. Moreover, we test whether ecology in terms of calling site could affect these relationships. We find that calling site has a major influence on acoustic allometry. Despite this, we identify only four major instances of allometric escape, potentially deriving from ecomorphological adaptations to new signal modalities. In these instances of allometric escape, the optima and strength of the scaling relationship are different than expected for most other frog species, representing new adaptive regimes of body size ~ call frequency. Allometric constraints on frog calls are highly conserved and have rarely allowed escape, despite frequent invasions of new adaptive regimes and dramatic ecomorphological divergence. Our results highlight the rare instances in which natural and sexual selection combined can overcome physical constraints on sound production. Abstract : Allometric constraints in frogs are highly conserved and have rarely promoted allometric escape despite frequent invasions of new adaptive regimes of sound frequency and dramatic ecomorphological divergence in body size and calling site. In this study, we highlight instances in which natural and sexual selection combined could overcome physical constraints on sound production.